2019
DOI: 10.1007/s11606-019-04841-x
|View full text |Cite
|
Sign up to set email alerts
|

How Have 30-Day Readmission Penalties Affected Racial Disparities in Readmissions?: an Analysis from 2007 to 2014 in Five US States

Abstract: BACKGROUND: Thirty-day readmission penalties implemented with the Hospital Readmission Reduction Program (HRRP) place a larger burden on safety-net hospitals which treat a disproportionate share of racial minorities, leading to concerns that already large racial disparities in readmissions could widen. OBJECTIVE: To examine whether there were changes in Black-White disparities in 30-day readmissions for acute myocardial infarction (AMI), congestive heart failure (CHF), or pneumonia following the passage and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…24 They may have a higher proportion of patients from disadvantaged groups, who are more likely to be discharged to an institution rather than to home 25 and who have higher readmission rates. 26 Safety-net hospitals may have a disproportionate number of patients with social and cultural challenges such as poor language skills, low health literacy, or lack of access to food, housing, and transportation. 27,28 To address the inequity of disproportionately penalizing hospitals that provide care to the most vulnerable patients, the 21st Century Cures Act of 2016 requires CMS to benchmark each hospital's performance compared with hospitals with similar characteristics, rather than all other hospitals.…”
Section: Overview Of the Hospital Readmissions Reduction Programmentioning
confidence: 99%
“…24 They may have a higher proportion of patients from disadvantaged groups, who are more likely to be discharged to an institution rather than to home 25 and who have higher readmission rates. 26 Safety-net hospitals may have a disproportionate number of patients with social and cultural challenges such as poor language skills, low health literacy, or lack of access to food, housing, and transportation. 27,28 To address the inequity of disproportionately penalizing hospitals that provide care to the most vulnerable patients, the 21st Century Cures Act of 2016 requires CMS to benchmark each hospital's performance compared with hospitals with similar characteristics, rather than all other hospitals.…”
Section: Overview Of the Hospital Readmissions Reduction Programmentioning
confidence: 99%
“…Researchers of other studies in adult populations have reported mixed results for racial and socioeconomic disparities in readmission rates over time. [24][25][26][27] Over half of pediatric admissions in the United States are covered by Medicaid, and this number has grown substantially under the Affordable Care Act and the Children's Health Insurance Program. 16,17 As such, this population represents an important target for readmission reduction efforts with the potential to significantly cut health care expenditures.…”
Section: Figurementioning
confidence: 99%
“…Evidence on the intended impacts of these programs has been mixed. Early research suggested that introduction of the HRRP was associated with a decline in targeted readmissions [ 3 ] and larger HRRP penalties may be associated with larger improvements [ 3 , 4 ]. More recent studies, however, suggest that reductions in readmissions attributed to HRRP may be overstated due to concurrent changes in electronic claim standards [ 5 ].…”
Section: Introductionmentioning
confidence: 99%